Surface-tectonic coupling at the Namche Barwa – Gyala Peri massif and geologic hazards associated with a proposed dam on the Yarlung-Tsangpo river in SE Tibet - Zeitler, Peter; Meltzer, Anne; Zurek, Brian; Brown, Lucy; Finnegan, Noah; Hallet, Bernard; Chamberlain, Page; Kidd, William; Koons, Peter (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1348 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.176